The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fvets.2021.799773
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Identification and Pharmacokinetic Behavior of Diaveridine in the Plasma of Pigs and Chickens Based on Radioactive Tracing Coupled With LC/MS-IT-TOF Assay

Abstract: Diaveridine (DVD) is widely used for the prevention and treatment of coccidiosis and leucocytozoonosis infections in food-producing animals. To gain a better understanding of DVD metabolism and pharmacokinetics in healthy Landrace/Doric Cross castrated male pigs and both female and male Cobb 500 broiler chickens, a method involving radioactive tracing coupled with LC/MS-IT-TOF was developed for the identification and quantitation of DVD and its metabolites in pig and chicken plasma, and then was applied to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The elevated levels of 2-hydroxycyclohexane-carboxylic acid, often found in foods and natural products (Wishart et al, 2022 ), reflect the unique dietary habits or the consumption of traditional medicines within the HIV-/TB+ cohort. Similarly, increased levels of diaveridine, an antibacterial agent used in animal feeds (Wang et al, 2022 ), suggest dietary exposure through animal products, with the highest levels in the HIV+/TB+ group indicating altered excretion and processing due to the compounded effects of both HIV and TB.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of 2-hydroxycyclohexane-carboxylic acid, often found in foods and natural products (Wishart et al, 2022 ), reflect the unique dietary habits or the consumption of traditional medicines within the HIV-/TB+ cohort. Similarly, increased levels of diaveridine, an antibacterial agent used in animal feeds (Wang et al, 2022 ), suggest dietary exposure through animal products, with the highest levels in the HIV+/TB+ group indicating altered excretion and processing due to the compounded effects of both HIV and TB.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that in swine, the weak biotransformation of DVD in chickens indicates that it will have a longer half-life. This presumption was supported by the pharmacokinetic parameters of DVD in the two species. , Only rats were shown to have a sulfonation metabolic pathway of DVD that resulted in the creation of the novel metabolite M5. Meanwhile, metabolite M3 was discovered in chickens and rats, whereas metabolite M4 was discovered in swine and chickens.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites were formed via O -demethylation, α-hydroxylation, benzene ring-hydroxylation, N-oxidation, 4′-methylation, NH 2 -glucuronidation, and O -demethylation-glucuronidation . In our previous study, DVD metabolites in pig and chicken plasma were identified by the radioactive tracing coupled with the LC/MS–IT–TOF method, and their kinetic parameters were profiled . However, DVD-related metabolites in excreta, the routes of excretion, mass balance, tissue distribution, and elimination remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation